2009
DOI: 10.1021/jf9002363
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Mechanical, and Barrier Properties of Cassava Starch−Chitosan Films Incorporated with Oregano Essential Oil

Abstract: The physicochemical and antimicrobial properties of starch-chitosan films incorporated with oregano essential oil (OEO) have been investigated. The antimicrobial effects of starch-chitosan-OEO films against Bacillus cereus, Escherichia coli, Salmonella enteritidis, and Staphylococcus aureus were determined by the disk inhibition zone method. The film mechanical properties, water vapor permeability (WVP), Fourier transform infrared spectra (FTIR), and thermograms (TGA) were also determined. Films added with OEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
197
3
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(243 citation statements)
references
References 27 publications
28
197
3
15
Order By: Relevance
“…They reported that this was due to the effect of the lipid on the starch chains and that the phase rich in polysaccharide had higher TS than the lipid phase. This result confirms the outcome of the work by Pelissari et al (2009) who had reported that incorporation of oregano oil in starch films increases its stretchability, however the results obtained by Bourtoom and Chinnan (2009) are different from those presented here.…”
Section: Mechanical Propertiessupporting
confidence: 88%
See 1 more Smart Citation
“…They reported that this was due to the effect of the lipid on the starch chains and that the phase rich in polysaccharide had higher TS than the lipid phase. This result confirms the outcome of the work by Pelissari et al (2009) who had reported that incorporation of oregano oil in starch films increases its stretchability, however the results obtained by Bourtoom and Chinnan (2009) are different from those presented here.…”
Section: Mechanical Propertiessupporting
confidence: 88%
“…Nevertheless, technological applications of starch reveal several disadvantages as a result of its inherently strongly hydrophilic character (water sensitivity) and poor mechanical properties compared to conventional synthetic polymers. This makes it unsatisfactory for some applications such as packaging (Pelissari et al, 2009) although some of these problems can potentially be solved with the addition of plasticizers. Glycerol has often been used as a plasticizer since it is compatible with amylose and as such, it improves the mechanical properties of films by decreasing intermolecular forces and interfering with amylose packing.…”
Section: Introductionmentioning
confidence: 99%
“…and are closer to those of the control film (oil-free chitosan film). A decrease in these two properties with the increase of oil was also observed in emulsified films with chitosan/basil essential oil [19] , chitosan/thyme essential oil [20] , chitosan/tea tree oil [22] , cassava starch-chitosan/oregano essential oil [33] , and whey protein/olive oil [34] .…”
Section: Mechanical Propertiesmentioning
confidence: 64%
“…Regardless, Figure 4 shows that both chitosan concentrations presented the same behaviour when the andiroba oil concentration increases. Pelissari et al [33] verified that the addition of oregano essential oil to chitosan-starch films did not influence the thermal stability of these films; however, they observed an increase in residue percentage after the incorporation of the oregano essential oil. Table 4.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Foi relatado por outros autores que a T max de filmes de pululana puros é de 299 °C, 12 enquanto que a T max de filmes de amido se localiza entre 250 e 350 °C. 26 Pode-se perceber que os valores de T max observados para os filmes de amido estão muito próximos dos valores relatados para os filmes de pululana, e também dos valores encontrados neste trabalho.…”
Section: Análise Termogravimétrica (Tga)unclassified